Front Matter Jurnal ASET (Akuntansi Riset) Vol 10 No 1 January-June 2018 - Setiawan, Yana (Universitas Pendidikan Indonesia, 2018)
Front Matter Jurnal ASET (Akuntansi Riset) Vol 10 No 1 January-June 2018